Impact of COVID-19 to customers switching intention in the food segments: The push, pull and mooring effects in consumer migration towards organic food. (July 2022) - Ghufran, Muhammad; Ali, Sumran; Ariyesti, Fitri Rini; Nawaz, Muhammad Asim; Aldieri, Luigi; Xiaobao, Peng
Highlights: Demand for organic food is flourishing during the COVID-19 pandemic in China. Push-pull mooring factors attract a consumer towards organic food adoption. Push factors positively impact consumer switching intention towards organic food. Switching costs influence the relationship between push factors and switching intention. Abstract: This article discusses the compelling challenges posed by the COVID-19 pandemic by examining how much a given conventional food sector is reliable and secure in providing healthy food. For this purpose, we relied on the push–pull-mooring (PPM) model to examine the consumer switching intentions from conventional food to organic food. To investigate this model, we utilised the quantitative method approach and collected 1000 valid responses from Chinese consumers for a better understanding of the consumer purchase and switching intention. Based on our findings, the COVID-19 pandemic strongly pushes Chinese consumer's intentions towards organic food, even though the organic food sector is relatively new in China, which started in the 1990 s and no such legitimate evidence found that the food processing or packaging caused COVID-19 transmission. This research assists the decision makers and managers to understand and analyse the true consumer switching intention that drastically changes because of pandemics and consumers are self-protecting from any harm. This article also helps policymakers see the basic problems like a high price, availability issues, and less credence attribute knowledge getting away to the consumer from organic food and ensuring the availability, affordable price, and awareness regarding credence attribute through reanalysing and implementation of policies.